The nuisance of distorting Begum Rokeya’s legacy - Hasan, Md. Mahmudul (The Daily Star, 2025)
Given Begum Rokeya's righteous lifestyle and innumerable affirmations of her faith, it is inconceivable that she would question the divine origin of Islam's primary texts. Her pointed critiques were directed at misogynistic texts written by self-styled custodians of Islam.